Produção e avaliação de duas proteínas quiméricas - PQ10 e PQ20 - quanto à imunogenicidade e uso em imunodiagnóstico para Leishmaniose visceral canina - Angelica Rosa Faria (2014)
Visceral leishmaniasis is the most severe form among leishmaniasis. The zoonotic disease, caused by Leishmania infantum, represents 20 % of the world's human visceral leishmaniasis with increasing incidence in urban areas of the tropics. In Brazil, one of the control measures is the identification and elimination of infected dogs. The diagnostic methods used to identify these animals are not able to detect 100 % of them, which may compromise the effectiveness of this control measure . Furthermore, the development of an effective vaccine would be highly desirable. Thus, to contribute to the diagnosis and control of Canine Visceral Leishmaniasis, we aimed to develop and test two new antigens. Previously, we published a work in which ten antigenic peptides were identified in ELISA anti - LVC. In the current proposal, these ten peptides were assembled into a synthetic gene. Furthermore, another twenty peptides were identified as good T cell epitopes in a publication by our group. Similarly, these peptides were joined in a molecule. Both genes have been cloned and expressed in Escherichia coli, producing two chimeric recombinant proteins, PQ10 and PQ20. These antigens have been used in ELISA anti-LVC with a sensitivity of 80.1% (PQ10) and 84.9% (PQ20) and specificity of 65.6% for both. The proteins were able to identify asymptomatic dogs (80%) more effectively than ELISA Biomanguinhos (0%) and DPP® (10%). Moreover, detection of dogs in the beginning of the infection also occurred, with positivities ranging from 23 and 65%, depending upon the phase in which sera was acquired. The proteins were immunogenic in the raising of polyclonal serum in rabbits. With this serum, we found that only a few peptides were the most responsible for the immunogenicity of the chimeric proteins. In mice immunization and in stimulation of canine peripheral blood mononuclear cells, we observed that the proteins stimulate a pattern of Th2 -type immune response, with IL-10 and IL-4 production. In summary, our studies demonstrate that the use of the constructed chimeric proteins based on B cells epitopes has a great potential in immunodiagnosis and can benefit canine visceral leishmaniasis control programs.